A "Valve‐Closing" Starvation Strategy for Amplification of Tumor‐Specific Chemotherapy. Issue 8 (17th January 2022) - Li, Xianglong; Jiang, Cong; Wang, Qinghua; Yang, Shaobo; Cao, Yuanyuan; Hao, Ji‐Na; Niu, Dechao; Chen, Yan; Han, Bo; Jia, Xin; Zhang, Peng; Li, Yongsheng
Abstract: Starvation‐dependent differential stress sensitization effect between normal and tumor cells provides a potentially promising strategy to amplify chemotherapy effects and reduce side effects. However, the conventional starvation approaches such as glucose oxidase (Gox)‐induced glucose depletion and nanomedicine‐enabled vascular embolism usually suffer from aggravated tumor hypoxia, systemic toxicity, and unpredictable metabolic syndrome. Herein, a novel "valve‐closing" starvation strategy is developed to amplify the chemotherapy effects via closing the "valve" of glucose transported into tumor cells, which is accomplished by a glucose transporters 1 (GLUT1, valve of glucose uptake) inhibitor (Genistein, Gen) and chemotherapeutic agent (Curcumin, Cur) coloaded hybrid organosilica‐micelles nanomedicine (designated as (Gen + Cur)@FOS) with controllable stability. In vitro and in vivo results demonstrate that (Gen + Cur)@FOS can effectively reduce glucose/adenosine triphosphate levels in tumor cells by inhibiting GLUT1 expression (i.e., "valve‐closing") to induce the starvation of tumor cells, thus weakening the resistance of tumor cells to apoptosis caused by chemotherapy, and consequently contributing to the remarkably improved antitumor efficiency and minimized side effects based on the stress sensitization effect mediated by GLUT1 inhibition‐induced starvation. This "valve‐closing" starvation strategy provides a promising paradigm for the development of novel nanotherapeutics with amplified chemotherapy effect. Abstract : A novel "valve‐closing" starvation strategy to amplify the chemotherapy effect is developed based on GSH‐responsive organosilica hybrid micelles encapsulated with glucose transporters 1 inhibitor genistein (Gen) and drug curcumin (Cur), in which Gen can effectively starve tumor cells to enhance their sensitivity to Cur and minimize side effects of chemotherapy by starvation‐mediated stress sensitization.